QUIZIZZ APLICATION ON STUDENTS’ WRITING ACHIEVEMENT AT SENIOR HIGH SCHOOL BANGKALAN - Wahyuni, Asri Dilla; Moh. Hafidz (Esteem Journal of English Education Study Programme, 2025)
The purpose of this study is to look into how the Quizizz application affects students' writing achievement in the tenth grade at Bangkalan Senior High School.  Writing is an essential ability for academic and professional success; nonetheless, many students struggle with grammar, sentence structure, and coherence, particularly in narrative works.  This study used a quasi-experimental design with 36 tenth-grade pupils. The data were gathered by pre- and post-tests and analyzed with SPSS.  The data show that using the Quizizz program considerably enhanced pupils' writing skills.  Quizizz increased student enthusiasm and involvement throughout writing lessons.  Based on the findings, it can be concluded that the Quizizz program is an effective digital tool for improving students' writing abilities, particularly in narrative text writing.  Thus, including Quizizz into English language instruction can improve the teaching and learning process.